Decompression in Chiari Malformation: Clinical, Ocular Motor, Cerebellar, and Vestibular Outcome - Goldschagg, Nicolina; Feil, Katharina; Ihl, Franziska; Krafczyk, Siegbert; Kunz, Mathias; Tonn, Jörg Christian; Strupp, Michael; Peraud, Aurelia (Frontiers in Neurology, 2017)
Background Treatment of Chiari malformation can include suboccipital decompression with resection of one cerebellar tonsil. Its effects on ocular motor and cerebellar function have not yet been systematically examined. Objective To investigate whether decompression, including resection of one cerebellar tonsil, leads to ocular motor, vestibular, or cerebellar deficits. Patients and methods Ten patients with Chiari malformation type 1 were systematically examined before and after (1 week and 3 months) suboccipital decompression with unilateral tonsillectomy. The work-up included a neurological and neuro-ophthalmological examination, vestibular function, posturography, and subjective scales. Cerebellar function was evaluated by ataxia rating scales. Results Decompression led to a major subjective improvement 3 months after surgery, especially regarding headache (5/5 patients), hyp-/dysesthesia (5/5 patients), ataxia of the upper limbs (4/5 patients), and paresis of the triceps and interosseal muscles (2/2 patients). Ocular motor disturbances before decompression were detected in 50% of the patients. These symptoms improved after surgery, but five patients had new persisting mild ocular motor deficits 3 months after decompression with unilateral tonsillectomy (i.e., smooth pursuit deficits, horizontally gaze-evoked nystagmus, rebound, and downbeat nystagmus) without any subjective complaints. Impaired vestibular (horizontal canal, saccular, and utricular) function improved in five of seven patients with impaired function before surgery. Posturographic measurements after surgery did not change significantly. Conclusion Decompression, including resection of one cerebellar tonsil, leads to an effective relief of patients’ preoperative complaints. It is a safe procedure when performed with the help of intraoperative electrophysiological monitoring, although mild ocular motor dysfunctions were seen in half of the patients, which were fortunately asymptomatic.